2020
DOI: 10.1155/2020/4141370
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Intensity and Associated Factors among Male Smokers in Ethiopia: Further Analysis of 2016 Ethiopian Demographic and Health Survey

Abstract: Background. Smoking invariably has health, social, economic, and environmental consequences in Ethiopia. Reducing and quitting cigarette smoking improves individual health and increases available household funds for food, education, and better economic productivity. Therefore, this study is aimed at assessing cigarette smoking intensity and associated factors among male smokers in Ethiopia. Methods. The data were extracted from the 2016 national cross-sectional Ethiopian Demographic and Health Survey. Our stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
3
1
Order By: Relevance
“…Regarding the rates of smoking and Khat consumption in males, our findings are in line with Ahmed and colleagues [ 8 ], but are higher than those of the SLHDS report 2020, which reported rates of 14.3% and 18.2%, respectively [ 7 ]. Considering the state of smoking in the neighbouring countries, our findings were higher than those in Kenya (13.5%) [ 26 , 27 ], Sudan (19.6%) [ 28 ] and Ethiopia (21.2%) [ 29 ], but were comparable to those in Yemen (33.1%) [ 30 ]. Globally, the prevalence of smoking was 36.7% in males and 7.8% in females in 2020 [ 31 ].…”
Section: Discussioncontrasting
confidence: 46%
“…Regarding the rates of smoking and Khat consumption in males, our findings are in line with Ahmed and colleagues [ 8 ], but are higher than those of the SLHDS report 2020, which reported rates of 14.3% and 18.2%, respectively [ 7 ]. Considering the state of smoking in the neighbouring countries, our findings were higher than those in Kenya (13.5%) [ 26 , 27 ], Sudan (19.6%) [ 28 ] and Ethiopia (21.2%) [ 29 ], but were comparable to those in Yemen (33.1%) [ 30 ]. Globally, the prevalence of smoking was 36.7% in males and 7.8% in females in 2020 [ 31 ].…”
Section: Discussioncontrasting
confidence: 46%
“…Manual workers smoked more also found in Ethiopia. 23 Sex, age, education level, occupation and household wealth were significantly associated with tobacco smoking in the Gambia. We found that the prevalence of tobacco smoking is comparatively higher among men than women.…”
Section: Discussionmentioning
confidence: 95%
“…The removal of DNA adducts requires DNA repair, which indicates that the variation of DNA repair genes may be related to the repair efficiency of different DNA damages [9]. In addition, there is competition among different detoxification pathways, and different individuals have different balance between metabolic activation and detoxification, thus affecting the risk of cancer [10]. For the tumor cases diagnosed for the first time by various medical institutions at all levels in the city, the outpatient or resident doctors shall fill in the Tumor Report Card, and the medical technology departments (pathology, CT/MRI, radiology, Bultrasound/color ultrasound, endoscope and blood testing center) shall establish the Tumor Register to timely record the information related to the diagnosis and treatment of malignant tumor cases in their departments.…”
Section: Research Objectmentioning
confidence: 99%